2017
DOI: 10.1177/1521025117735292
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interrelationships Among Academic Entitlement, Academic Performance, and Satisfaction With Life in a College Student Sample

Abstract: The purpose of this study was to explore the relationship among academic entitlement, life satisfaction, and academic performance as measured by cumulative grade point average. When comparing academically at-risk versus non-at-risk college students, academically at-risk students scored significantly lower on satisfaction with life than their non-at-risk peers. In addition, a significant negative correlation was found between academic entitlement and satisfaction with life for all students. Implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
4
14
0
Order By: Relevance
“…Due to this perception, students were encouraged to commit academic frauds (Luckett et al, 2017). Academic entitlement included not only sense of right in academic field they thought they were ought to obtain, rather academic entitlement was also associated with problematic behavior such as academic frauds (Reysen et al, 2017). In their research, Sohr-preston & Boswell (2015) revealed that academic frauds served as one of academic entitlement factors.…”
Section: Influence Of Academic Entitlement On Academic Fraudsmentioning
confidence: 99%
“…Due to this perception, students were encouraged to commit academic frauds (Luckett et al, 2017). Academic entitlement included not only sense of right in academic field they thought they were ought to obtain, rather academic entitlement was also associated with problematic behavior such as academic frauds (Reysen et al, 2017). In their research, Sohr-preston & Boswell (2015) revealed that academic frauds served as one of academic entitlement factors.…”
Section: Influence Of Academic Entitlement On Academic Fraudsmentioning
confidence: 99%
“…Nevertheless, stressful situations are not related exclusively to those with high GPA-according to Garber et al [12] poor academic performance also increases stress levels. Although the authors do agree that the stress that accompanies achieving a high GPA score is a direct threat to life satisfaction of university students [13], it is not the only academic trigger that influences LS decline-this phenomenon may correlate with the learning environment [14], education quality [15] or limitations placed on acquiring financial support for funding one's education [16].…”
Section: Introductionmentioning
confidence: 97%
“…Another interesting variable that could reasonably affect academic performance is academic entitlement. However, Reysen (2013) found no significant relationship between educational entitlement and academic performance. Similarly, Mallett (2009) found that global selfesteem has no significant impact on academic performance.…”
Section: Introductionmentioning
confidence: 77%